Concomitant of inside-shareholding, group affiliation and firm value: evidence from Pakistan - Waseemullah,; Tahir, Safdar Husain; Kaleem, Muhammad Shafiq; Kanwal, Tahirah; Quddoos, Muhammad Umer (Business: Theory and Practice, 2021)
The present study inspects the comparative effects of inside shareholding on firm value for group-affiliated firms and non-group-affiliated firms in Pakistan. The research uses the excess-value as a performance measure by employing a chop-shop approach in treatment effects regression model (TERM). The results reveal that lower level and higher level inside shareholding negatively associated with firms’ value. However, it positively relates at a moderate level. Also, inside shareholding-value relationship differs significantly for group-affiliated firms and non-group-affiliated firms. Firms with inside shareholding at lower level appear to more visible in business groups, and these firms show adverse firms’ value consistent with divergence of interest effect. Nevertheless, inside ownership firms at a higher level, namely standalone firms, negatively affect firm value with entrenchment effect. The findings also confirm non-linearity in inside shareholding-firm value relationships.